Tudáshálózat, avagy a szürreális kooperáció lehetősége a felsőoktatásban - Fábián, Attila; Koloszár, László (Közép-Európai Közlemények, 2017)
Among the companies it is already well known that their long term competitiveness is mostly specified by developing their basic and possibly exclusive knowledge. Nowadays this is more and more valid in the competition of higher educations. Only the biggest universities have resources to create and maintain the competitive knowledge and expertise in the whole dimension of the educational services. The smaller universities have to decide, how to develop their core competence. An option is to create an educational and research network with other similar-sized universities so that they shape themselves to become big university by avoiding unnecessary integration with other institutions. Core competence means when an institution or a faculty has such a special knowledge, which is typical for its operation and is the only owner of it. Because of this the core competence is the main guarantee for competitiveness. Every university and faculty management should aim to find the „fundamental competence”, which is also the basis for long-run competitiveness. In the European education system, the good chosen „competence” of universities has strengthened their identity and has increased the efficiency of their performance quality. The article also deals with the so often mentioned significance of the corporate and entrepreneurial background.